2011
DOI: 10.1097/gim.0b013e3182241d88
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of family history for cancer screening and referral in primary care: A report from the Family Healthware Impact Trial

Abstract: Purpose To assess the effectiveness of computerized familial risk assessment and tailored messages for identifying individuals for targeted cancer prevention strategies and motivating behavior change. Methods We conducted a randomized clinical trial in primary care patients aged 35–65 years using Family Healthware, a self-administered, internet-based tool that collects family history for six common diseases including breast cancer, colon cancer, and ovarian cancer, stratifies risk into three tiers, and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 38 publications
3
80
0
Order By: Relevance
“…This direct experience of a disease has greater impact on susceptibility perceptions than indirect or objective susceptibility information (Weinstein, 1989). Indeed, Rubinstein et al (2011) showed that a (family) history of a specific illness is associated with a higher perceived susceptibility to that illness. Similar findings are reported by Finney Rutten and Iannotti (2003) and Spector et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…This direct experience of a disease has greater impact on susceptibility perceptions than indirect or objective susceptibility information (Weinstein, 1989). Indeed, Rubinstein et al (2011) showed that a (family) history of a specific illness is associated with a higher perceived susceptibility to that illness. Similar findings are reported by Finney Rutten and Iannotti (2003) and Spector et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, our population was similar to those in comparable studies, which suggests that the population may be generalizable. 4,6,[9][10][11] Based on the results of this pilot study, MeTree is now being studied in five diverse national health-care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of these tools have shown that 42-82% of the general population are at increased risk for at least one condition depending on the number and type of diseases included in the risk assessment, and most do not know that they are at risk. 4,6,[9][10][11] The improved identification of increased-risk individuals suggests that there could be a clinically useful role for risk-assessment tools like these, particularly if they are coupled with clinical decision support (CDS). However, prior to promoting widespread integration within primary care, questions about integration into clinical workflow and clinical utility should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…9,15 Clinical trials of Family Healthware, an interactive online tool developed by the Centers for Disease Control and Prevention that stratifies familial risk for colon, breast, and ovarian cancer (among other diseases), showed at least 34% of adult primary-care users were at high risk or moderate risk for at least one of these three cancer types. 15 Likewise, the MeTree family history assessment tool, utilized in an unselected primary-care population, noted that 44% of patient users met higher risk criteria for increased management/prevention for breast/ovarian cancer, colon cancer, hereditary cancer syndromes, or thrombosis. 27 In our series, 128 of 159 (80.5%) of the Family HealthLink assignments across both cohorts were corroborated by a genetic counselor.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 Individuals with early-onset disease tend to have a stronger hereditary component, and the risk for family members is increased. [12][13][14][15] Identification of individuals at increased risk allows for presymptomatic screening and disease detection, as well as appropriate referral for genetic counseling and testing. 4,5 Despite growing evidence regarding the importance and efficacy of using family history, and the need for health-care providers to have family history triage tools for personalized health-care delivery, [16][17][18][19][20] this type of approach has not been broadly applied in clinical practice.…”
Section: Introductionmentioning
confidence: 99%